Human ribosomal protein L13a is dispensable for canonical ribosome function but indispensable for efficient rRNA methylation - Chaudhuri, Sujan (Cold Spring Harbor Laboratory Press, 2007)
Previously, we demonstrated that treatment of monocytic cells with IFN-γ causes release of ribosomal protein L13a from the 60S ribosome and subsequent translational silencing of Ceruloplasmin (Cp) mRNA. Here, evidence using cultured cells demonstrates that Cp mRNA silencing is dependent on L13a and that L13a-deficient ribosomes are competent for global translational activity. Human monocytic U937 cells were stably transfected with two different shRNA sequences for L13a and clonally selected for more than 98% abrogation of total L13a expression. Metabolic labeling of these cells showed rescue of Cp translation from the IFN-γ mediated translational silencing activity. Depletion of L13a caused significant reduction of methylation of ribosomal RNA and of cap-independent translation mediated by Internal Ribosome Entry Site (IRES) elements derived from p27, p53, and SNAT2 mRNAs. However, no significant differences in the ribosomal RNA processing, polysome formation, global translational activity, translational fidelity, and cell proliferation were observed between L13a-deficient and wild-type control cells. These results support the notion that ribosome can serve as a depot for releasable translation-regulatory factors unrelated to its basal polypeptide synthetic function. Unlike mammalian cells, the L13a homolog in yeast is indispensable for growth. Thus, L13a may have evolved from an essential ribosomal protein in lower eukaryotes to having a role as a dispensable extra-ribosomal function in higher eukaryotes.